Classification and identification of risk management techniques for mitigating risks with factor analysis technique in software risk management - Abdelrafe, Elzamly; Burairah, Hussin (Pak Publishing Group, 2015)
Regardless how much effort we put for the success of software projects, many software projects have a very high failure risk rate. The failure risk is not always avoidable, but it could be controllable by using risk management technique through the software development Lifecycle. The aim of this study is to present the factor analysis techniques to classify and identify the risk management techniques in the software development project. The best thirty risk management techniques were presented to respondents and all risk management techniques are used most of the time, and often. We have chosen three components: Planning and requirement techniques, communication techniques, models and tools for thirty risk management techniques. The study has been conducted on a group of software project managers in software development companies. We will intend to apply these study results on a real-world software project to verify the effectiveness of the risk management techniques on a software project for mitigating risks. Successful identifying of risk management techniques will greatly improve the probability of mitigating software risk.